Molecular and cellular regulation of wound healing; what goes wrong when wounds fail to heal or heal too much? - Schultz, Gregory (Henry Stewart Talks, 2014)
Sequence of Molecular and Cellular Events in Skin Wound Healing, Hemostasis, Inflammation, Repair and Remodelling, Chronic wounds, Role of matrix metalloproteinases in wound healing, Wound Bed Preparation and ‘T I M E’, Pathological Scarring, Treatments to reduce scarring
Reviewed at 2022/10/11